The Performance Comparison of Printed Dipole Antenna with Two Different Structures of AMC Ground Plane - Abu, Maisarah; A. Rahim, Mohamad Kamal; Suaidi, Mohd. Kadim; Mohd. Ibrahim, Imran; Md Nor, Norazura (2011)
The performances of the triple-band meandered dipole antenna backed by two different Artificial Magnetic Conductor (AMC) structures are discussed in this paper. Two kinds of AMC structures are presented namely rectangular-patch with rectangular slot and rectangular-patch with slotted rectangular and I-shaped slot. The AMCs are designed to operate at 0.92GHz and 2.45GHz. The performances of the antenna with and without the dual-band AMC ground plane are investigated in terms of return loss, realized gain and power received. It clearly shows that the printed dipole antenna has a lower gain compared to the printed dipole antenna with high-impedance structure ground plane (GP). Furthermore, the received power of the dipole antenna backed by the 2x2 rectangular-patch with slotted rectangular and I-slot AMC receives a slightly higher power compared to the dipole antenna backed by the 2x2 rectangularpatch with rectangular slot AMC.